Community-led initiatives for climate adaptation and mitigation. (2nd January 2020) - Simon, Katy; Diprose, Gradon; Thomas, Amanda C.
ABSTRACT: Planning for climate change is complex. There is some uncertainty about how quickly the climate will change and what the anticipated localised effects will be. There are also governance questions, for instance, who has the mandate to make decisions around the management of collective resources (like council infrastructure) and private property. Underlying these questions are issues of justice, equity and agency – who pays for the costs of adaptation and mitigation, and how do decision-makers engage with communities when what is ultimately needed is transformational socio-economic change? We use a case study in Te Awa Kairangi – Lower Hutt, Wellington, to show how a community initiative called Common Unity Project Aotearoa (CUPA) is fostering everyday practices of adaptation and mitigation amongst people who have traditionally had limited participation in more formal planning processes. We use the example of CUPA to demonstrate the significance of local community-led development initiatives for adapting to a changing climate. We argue that local government engagement with people around climate change cannot be separated from broader community development and wellbeing initiatives, and needs to be understood as longer term processes, rather than one-off project consultations.